2019
DOI: 10.1093/jas/skz280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brassica carinata meal as a protein supplement for growing beef heifers1,2

Abstract: Brassica carinata is a new oilseed crop in Florida with the potential of producing high-quality jet biofuel. A high-protein meal (~40% crude protein; CP) is obtained as a byproduct of oil extraction; however, limited research is available on the utilization of this meal as a protein supplement for beef cattle. A generalized randomized block design was used to evaluate the effects of supplementation with B. carinata meal pellets on performance and attainment of puberty in growing beef heifers consuming bermudag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…However, carinata meal must contain less than 2.0% erucic acid and less than 30 μmol g −1 of GSLs like sinigrin due to their detrimental effects on the health of animals by reducing palatability and interfering with iodine uptake (Nega & Woldes, 2018;Tripathi & Mishra, 2007). Therefore, carinata meal is restricted to 10% of the total diet or 0.3% of body weight per day (Paula et al, 2019;Schulmeister et al, 2019). The seed meal containing high GSL levels (44-168 μmol g −1 ) can be used as a soil amendment due to its biofumigant properties to suppress pest and disease activity (Gimsing & Kirkegaard, 2009;Mazzola & Manici, 2012;Pattison et al, 2006).…”
Section: Seed Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, carinata meal must contain less than 2.0% erucic acid and less than 30 μmol g −1 of GSLs like sinigrin due to their detrimental effects on the health of animals by reducing palatability and interfering with iodine uptake (Nega & Woldes, 2018;Tripathi & Mishra, 2007). Therefore, carinata meal is restricted to 10% of the total diet or 0.3% of body weight per day (Paula et al, 2019;Schulmeister et al, 2019). The seed meal containing high GSL levels (44-168 μmol g −1 ) can be used as a soil amendment due to its biofumigant properties to suppress pest and disease activity (Gimsing & Kirkegaard, 2009;Mazzola & Manici, 2012;Pattison et al, 2006).…”
Section: Seed Qualitymentioning
confidence: 99%
“…Carinata is widely adaptable to diverse growing regions, cropping systems, and management regimes with demonstrated potential to be grown on the continents of Asia, Africa, North America, South America, Europe, and Australia either as a spring or winter crop in double-cropped systems. Carinata is a biomolecular platform for fuel, meal, and co-products (McVetty et al, 2016;Schulmeister et al, 2019;Taylor et al, 2010) shown to increase farmer incomes and provide ecosystem goods and services (Basili & Rossi, 2018;Christ et al, 2020). Producers need to connect the ancillary value of growing carinata in their rotation with their entire cropping system.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits allow the production of carinata as a high-energy biofuel crop, with less energy required during processing and having similar physical and chemical properties and performance compared to petroleum-based jet fuel, with the potential to produce 50% less greenhouse gas emissions (Cardone et al, 2003;Choudhary et al, 2000;Seepaul et al, 2016;. Due to its high protein content and low fiber content, carinata seed can also be used to produce meal for animal feed after oil extraction, provided that it has undergone processing to reduce glucosinolate content to levels safe for animal health (Rosenthal et al, 2017;Schulmeister et al, 2019;Xin & Yu, 2014). Carinata seeds are also a source of sinapic acid, a starting material for organic and polymer synthesis (Shen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Glucosinolates occur in plants of the Brassica genus of the mustard family, including cabbage, broccoli, rapeseed, and carinata. Rapeseed (canola) and carinata meal can be used as livestock feed, but the presence of glucosinolates needs to be considered in a risk assessment (Schulmeister et al 2019; Scientific Panel on Contaminants in the Food Chain 2008). Caution is advised when using new alternative feed ingredients or industrial by-products that may contain high levels of antinutrients.…”
Section: What Are the Chemical Hazards To Consider? Naturally Occurringmentioning
confidence: 99%